Website-Based Stock and Cashier System with Scrum for Micro, Small, and Medium Enterprises: Sistem Stok dan Kasir Berbasis Website dengan Scrum untuk Usaha Mikro, Kecil, dan Menengah - Prakoso, Agustian; Habiba, Azifa (Indonesian Journal of Innovation Studies, 2025)
General background: Micro, Small, and Medium Enterprises (MSMEs) often rely on manual recording systems that are prone to errors and inefficiencies. Specific background: Distribution agents play a vital role in connecting producers and consumers, but conventional stock and cashier processes hinder data accuracy and decision-making. Knowledge gap: Previous studies usually separate inventory and cashier systems or lack structured development approaches. Aims: This study develops an integrated web-based stock and cashier system tailored for MSME distribution agents using Scrum methodology and FIFO principles. Results: The application was built with Laravel 11, Livewire, and Tailwind CSS. Usability testing using the System Usability Scale (SUS) yielded an average score of 78.6, categorized as good. The system reduced risks of data loss, enabled real-time stock monitoring, and supported customer relationship management. Novelty: Unlike earlier works, the system combines stock and cashier management in one platform, developed iteratively with Scrum, ensuring adaptability to user needs. Implications: The system strengthens operational efficiency, enhances data-driven decision-making, and supports the economic sustainability of MSMEs. Highlights The system integrates stock recording and cashier functions in one platform. Scrum methodology allowed adaptive and iterative system development. Usability testing confirmed good acceptance among users. Keywords: Web Application, Stock Management, Scrum Method, FIFO Technique, Usability Testing